173 Grazing Cover Crops: Effects of Cattle Removal Date on Forage Production and Cattle Performance. (8th October 2021) - Carrell, Russell C; Dillard, Sandra L; Mullenix, Mary K; Gamble, Audrey; Muntifering, Russ B
Abstract: Use of cool-season annual cover crops through grazing has been shown to be a potential tool in extending the grazing season, while still mitigating environmental risks associated with warm-season row crop production. Although data describing the effects of grazing on soil health are not novel, effects of grazing length on animal performance and cover crop production are limited. The objective was to determine cattle performance and forage production when grazing a cool-season annual cover-crop. Twelve, 1.2-ha pastures were established in a four species forage mix and randomly allocated to be grazed through either mid-February (FEB), mid-March (MAR), or mid-April (APR) with a non-grazed control (CON). Three tester steers were randomly placed in each paddock and a 1:1 forage allowance was maintained in each paddock using put-and-take steers. Animals were weighed every 30 d for determination of average daily gain (ADG). Forage was harvested bi-weekly and analyzed for forage production, neutral detergent fiber (NDF), and acid detergent fiber (ADF). Fiber fractions were measured using an ANKOM fiber analyzer (ANKOM Tech, Macedon, NY). All data were analyzed using MIXED procedure of SAS version 9.4 (SAS Inst., Cary, NC). Differences in forage mass were detected between CON and FEB (3, 694.75 vs. 2, 539.68 kg/ha; P < 0.003), CON and MAR (3, 694.75 vs. 1, 823.45 kg/ha; P < 0.001), and CON and APR (3, 694.75 vs. 1, 976.23 kg/ha; P < 0.001). Differences in total gain/acre were detected between APR and MAR (212.24 vs. 101.74 kg/ha; P < 0.0001), APR and FEB (212.24 vs 52.65 kg/ha; P < 0.0001), and FEB and MAR (101.74 vs. 52.65 kg/ha; P < 0.003). No differences were detected for tester ADG (1.23 kg/day, P = 0.56), NDF (44.9%, P = 0.99), or ADF (27.2%, P = 0.92) among treatments. These results indicate that cattle removal date effected forage yield and total gain/hectare.